Analisis Kestabilan dan Kontrol Optimal Model Penyebaran Penyakit Zika dari Gejala Dengue Menggunakan Forward Backward Sweep Method - Rahmalia, Dinita; Rohmatullah, Arif (Universitas Dr. Soetomo, 2019)
Abstract Zika disease is caused by zika virus. Zika virus can be contagiuous through the Aedes biting, such as Aedes aegypti. The mosquitoes can also transmit dengue fever. From the problem of zika spread, then in this research can be constructed mathematical model of zika spread from dengue symptoms. In zika spread from dengue symptoms, there are two populations included i.e. human population as host and mosquito population as vector. From mathematical model of zika spread, there are two equilibrium points such as disease free equilibrium and endemic equilibrium. In this research, from mathematical model of zika spread from dengue symptoms, it will be added control such as vaccination. The method used for solving optimal control problem and resulting numerical solutions is Forward Backward Sweep Method. Based on simulation results, control given such as vaccination to susceptible human can reduce zika spread to be minimum. Keywords: Stability Analysis, Infectious Disease Model, Optimal Control, Forward Backward Sweep Method, Runge Kutta Abstrak Penyakit zika disebabkan oleh virus zika. Virus zika dapat menular melalui gigitan nyamuk Aedes, terutama Aedes aegypti. Nyamuk tersebut juga mentransmisikan penyakit demam berdarah (dengue). Dari permasalahan penyebaran penyakit zika, maka pada penelitian ini dapat dibuat model matematika penyebaran penyakit zika dari gejala dengue. Dalam penyebaran penyakit zika dari gejala dengue, terdapat dua populasi yang terlibat yaitu populasi manusia sebagai host dan populasi nyamuk sebagai vektor. Dari model matematika penyebaran penyakit zika, terdapat dua titik kesetimbangan yaitu titik kesetimbangan bebas penyakit dan titik kesetimbangan endemik. Pada penelitian ini, dari model matematika penyebaran penyakit zika dari gejala dengue, akan ditambah kontrol berupa vaksinasi. Metode yang digunakan untuk menyelesaikan masalah kontrol optimal dan menghasilkan solusi numerik adalah Forward Backward Sweep Method. Berdasarkan hasil simulasi, pemberian kontrol berupa vaksinasi pada manusia susceptible dapat mengendalikan penyebaran penyakit zika menjadi lebih minimum. Kata Kunci: Analisis Kestabilan, Model Penyakit Menular, Kontrol Optimal, Forward Backward Sweep Method, Runge Kutta